Comparison of pregnant women from public and private health care: a psychological approach - Juliana Fernandes Filgueiras Meireles; Clara Mockdece Neves; Marcella Fernandes Paticcié Nacif; Pedro Henrique Berbert de Carvalho; Maria Elisa Caputo Ferreira
Abstract Objectives: to compare sociodemographic, anthropometric and psychological factors in pregnant women receiving public and private health care, as well as verify the influence of eating attitudes, depressive symptoms, self-esteem and anxiety on body attitudes in both sectors. Methods: this study included 386 pregnant women aged 18-46 (mean of 29.32 ± 6.04 years). Instruments were applied to evaluate body attitudes, eating attitudes, depressive symptoms, self-esteem and anxiety. Anthropometric and obstetric data were collected. Descriptive, comparative and correlational analyses were performed. Results: troubled sociodemographic characteristics, negative body attitudes, inappropriate eating attitudes, depressive symptoms, low self-esteem, and high levels of trait and state anxiety were significantly higher among participants receiving public health care (p<0.05). Eating attitudes and self-esteem directly influenced the body attitudes of those receiving public health care (R2 adjusted=0.336, p<0.001) and private health care (R2 adjusted=0.324, p<0.001). Conclusions: it was concluded that the sociodemographic, anthropometric, and psychological factors were more worrying in pregnant women receiving care in the public sector when compared to those of the private sector.